Physiological responses of Arundo donax ecotypes to drought: a common garden study. Issue 1 (26th April 2016) - Haworth, Matthew; Cosentino, Salvatore Luciano; Marino, Giovanni; Brunetti, Cecilia; Scordia, Danilo; Testa, Giorgio; Riggi, Ezio; Avola, Giovanni; Loreto, Francesco; Centritto, Mauro
Abstract: Genetic analyses have suggested that the clonal reproduction of Arundo donax has resulted in low genetic diversity. However, an earlier common garden phenotyping experiment identified specimens of A. donax with contrasting biomass yields (ecotypes 6 and 20). We utilized the same well‐established stands to investigate the photosynthetic and stress physiology of the A. donax ecotypes under irrigated and drought conditions. Ecotype 6 produced the largest yields in both treatments. The A. donax ecotypes exhibited identical high leaf‐level rates of photosynthesis ( P N ) and stomatal conductance ( G s ) in the well‐watered treatment. Soil drying induced reductions in P N and G s, decreased use of light energy for photochemistry, impaired function of photosystem II and increased heat dissipation similarly in the two ecotypes. Levels of biologically active free‐abscisic acid (ABA) and fixed glycosylated‐ABA increased earlier in response to the onset of water deficit in ecotype 6; however, as drought progressed, the ecotypes showed similar increases in both forms of ABA. This may suggest that because of the low genetic variability in A. donax the genes responding to drought might have been activated similarly in the two ecotypes, resulting in identical physiological responses to water deficit. Despite the lack of physiological ecotypic differences that could be associated with yield, A. donax retained a high degree of P N and biomass gain under water deficit stress conditions. This may enable utilization of A. donax as a fast growing biomass crop in rain‐fed marginal lands in hot drought prone climates.